Removing backscatter to enhance the visibility of underwater objects - Tang, Xiaoyu (2017)
Underwater vision enhancement is a vital issue in ocean engineering and backscatter removing is widely used in the restoration procedure. With the development of ocean engineering and the increasing of ocean exploration, image and video are essential means to obtain and record information. However, underwater images and videos always suffer from low contrast and color distortion due to the existence of dust-like particles and light attenuation. As a result, method to restore underwater videos and images has been drawn more and more attention. In this dissertation, the physical process of underwater light propagation is analyzed. The proposed method is based on optical haze model and fusion of adjacent frames. The procedure mainly includes: background light estimation, block-based transmission estimation and refinement; background light fusion between sequential frames and transmission fusion among adjacent frames; haze removal based on haze model; color correction by stretching pixel values. Both subjective and objective measurements are adopted to evaluate and compare the results of the proposed method and other state-of-the-art methods. The results of the proposed method show that it could enhance the visibility and fidelity of underwater scenes in videos, especially in open scenes with dense haze in deep sea environment. Also, the proposed method could achieve great clearness in underwater scenes while keeping the contrast and resolution at a proper level.